Bridging the Gap: Tribal Education in India – Challenges and Opportunities - Dr Sudnyani Biradar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This article is a conceptual frame work and understanding related to tribal education in India scenario study conducted with both primary and secondary sources of data. The present structure of the society and its diversity within the cave of caste system in India projected through critical analysis. Integration of development theory and practices contextually in India and special need focusing towards the tribal education policy prospects and need also. The firsthand experience of different social reformers, educates and also critically examined with statement forms in the article. Suggestions and need based education in the provision of Indian constitutions are drawn time to time in order to strengthen the need based education specific to Tribal Education system of India. Lastly the suggestions are also given for the uplift of the provision as tribal education of India. However, based on the analysis of the factors contributing to non- enrolment and/or dropout and descriptions of case studies, it is evident that there needs to be more philanthropic investment outside the classroom too. This would provide a solid foundation that leverages these assets and develops stronger individual potential that can transcend the barriers experienced by tribal today.